Haemato-Biochemical Alterations in Cattle Naturally Infected with Lumpy Skin Disease - Raval, Jigar B; Raval, Sunant K; Kanani, Amit N; Sadhu, Dashrath B (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Lumpy skin disease (LSD) is an emerging viral disease of cattle, causing substantial economic losses due to decreased productivity and  increased morbidity. This study investigated haematological and biochemical alterations in LSD-affected cattle (n=150) compared to  healthy controls (Group A, n=25). LSD-infected animals were categorised according to the severity of infection based on clinical signs  in to Group B: Mild LSD infection (n=42), Group C: Moderate LSD infection (n=84), and Group D: Severe LSD infection (n=24). Infected  animals exhibited significant leukopenia, lymphopenia, neutrophilia, macrocytic hypochromic anaemia, and thrombocytopenia in  accordance with the severity of the disease. Biochemical analysis showed reduced total protein and albumin with elevated blood urea  nitrogen, creatinine, ALT, and AST, particularly in severe cases, and these alterations were also in accordance with the severity of the  disease. The values of almost all haemato-biochemical parameters were significantly (p
Keywords: Cattle, Diagnosis, Haematology, Lumpy skin disease, Serum biochemistry